Broadband critical dynamics in disordered lead-based perovskites*Article In Memoriam of Professor Roger A Cowley. (18th June 2020) - Stock, C; Songvilay, M; Gehring, P M; Xu, Guangyong; Roessli, B
Abstract: Materials based on the cubic perovskite unit cell continue to provide the basis for technologically important materials with two notable recent examples being lead-based relaxor piezoelectrics and lead-based organic–inorganic halide photovoltaics. These materials carry considerable disorder, arising from site substitution in relaxors and molecular vibrations in the organic–inorganics, yet much of our understanding of these systems derives from the initial classic work of Prof. Roger A Cowley, who applied both theory and neutron scattering methods while at Chalk River Laboratories to the study of lattice vibrations in SrTiO3 . Neutron scattering continues to play a vital role in characterizing lattice vibrations in perovskites owing to the simple cross section and the wide range of energy resolutions achievable with current neutron instrumentation. We discuss the dynamics that drive the phase transitions in the relaxors and organic–inorganic lead-halides in terms of neutron scattering and compare them to those in phase transitions associated with a 'central peak' and also a soft mode. We review some of the past experimental work on these materials and present new data from high-resolution time-of-flight backscattering spectroscopy taken on organic–inorganic perovskites. We will show that the structural transitions in disordered lead-based perovskites are driven by a broad frequency band of excitations.